Inhibiting Glycolysis and ATP Production Attenuates IL-33-Mediated Mast Cell Function and Peritonitis - Caslin, Heather L.; Taruselli, Marcela T.; Haque, Tamara; Pondicherry, Neha; Baldwin, Elizabeth A.; Barnstein, Brian O.; Ryan, John J. (Frontiers in Immunology, 2018)
Cellular metabolism and energy sensing pathways are closely linked to inflammation, but there is little understanding of how these pathways affect mast cell function. Mast cells are major effectors of allergy and asthma, and can be activated by the alarmin IL-33, which is linked to allergic disease. Therefore, we investigated the metabolic requirements for IL-33-induced mast cell function, to identify targets for controlling inflammation. We found that IL-33 increases glycolysis, glycolytic protein expression, and oxidative phosphorylation (OX PHOS). Inhibiting OX PHOS had no effect on cytokine production, but glycolysis antagonism with 2-deoxyglucose or oxamate suppressed inflammatory cytokine production in vitro and in vivo. ATP reversed this suppression. Glycolytic blockade suppressed IL-33 signaling, including ERK phosphorylation, NFB transcription, and ROS production in vitro, and suppressed IL-33-induced neutrophil recruitment in vivo. To test a clinically relevant way to modulate these pathways, we examined the effects of the FDA-approved drug metformin on IL-33 activation. Metformin activates AMPK, which suppresses glycolysis in immune cells. We found that metformin suppressed cytokine production in vitro and in vivo, effects that were reversed by ATP, mimicking the actions of the glycolytic inhibitors we tested. These data suggest that glycolytic ATP production is important for IL-33-induced mast cell activation, and that targeting this pathway may be useful in allergic disease.